2021
DOI: 10.1002/bmc.5126
|View full text |Cite
|
Sign up to set email alerts
|

Levels of residues and dietary risk assessment of the fungicides myclobutanil, penconazole, tebuconazole, and triadimenol in squash

Abstract: Triazole fungicides may potentially harm human health. The 'quick, easy, cheap, effective, rugged, and safe' approach has become popular for extraction and cleanup during pesticide residue analysis. We aimed to (a) validate a method for the simultaneous determination of myclobutanil, penconazole, tebuconazole, and triadimenol in squash using LC-MS/MS and (b) determine the pre-harvest intervals (PHIs) and assess the related risk of consuming squash cultivated under open-field conditions in Saudi Arabia. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…At present, the main detection and analytical methods for the aforementioned pesticides are gas chromatography-electron capture detection (GC-ECD), gas chromatography-mass spectrometry (GC-MS), high-performance liquid chromatography (HPLC), and HPLC-mass spectrometry (HPLC-MS/MS) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The main matrix includes vegetables such as broccoli and zucchini, fruits such as pears and apples, and traditional Chinese medicine [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Few studies have reported on multiresidue analysis of pesticides and their metabolites in litchi and longan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the main detection and analytical methods for the aforementioned pesticides are gas chromatography-electron capture detection (GC-ECD), gas chromatography-mass spectrometry (GC-MS), high-performance liquid chromatography (HPLC), and HPLC-mass spectrometry (HPLC-MS/MS) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The main matrix includes vegetables such as broccoli and zucchini, fruits such as pears and apples, and traditional Chinese medicine [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Few studies have reported on multiresidue analysis of pesticides and their metabolites in litchi and longan.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on multiresidue analysis of pesticides and their metabolites in litchi and longan. Common sample purification methods include solid phase extraction (SPE), liquid–liquid distribution extraction, and QuEChERS [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. SPE is a tedious and time-consuming method involving the use of a large amount of organic solvents and nitrogen blowing, which is relatively cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that myclobutanil persists in the environment and accumulates along the food chain, which may threaten human health and environmental pollution (Sun et al 2014). In recent years, there are many reports about the residues of myclobutanil in agricultural products and environmental samples, including the pretreatment method (Deng et al 2010), the dissipation dynamic(Hwang &Kim 2013, Wang et al 2012), the level of myclobutanil residues in the actual samples (Abdallah et al 2021, Lou et al 2008) which has caused public concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the European Union (EU) they are set for squash fruit only(EU Pesticides Database, 2021).The MRL valuesfor squash fruit in the EU and the ROK are 0.5 and 1.5 mg/kg for dimethomorph, 0.3 mg/kg and undetermined for mandipropamid, 0.3 and 0.1 mg/kg for myclobutanil, and 0.01 and 0.2 mg/kg for metalaxyl, respectively.In the case of squash fruit, previous studies reported on dissipation pattern and exposure risk assessment ofchlorfenapyr(Abdel Ghani and Abdallah, 2016),sulfoxa or(O. Abdallah et al, 2021), tebuconazole, penconazole, myclobutnil, and triadimenol(O. I. Abdallah et al, 2021).However, there are no publications on dissipation pattern or human exposure risk assessment of any pesticide in squash leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Abdallah et al, 2021), tebuconazole, penconazole, myclobutnil, and triadimenol(O. I. Abdallah et al, 2021).However, there are no publications on dissipation pattern or human exposure risk assessment of any pesticide in squash leaf.…”
Section: Introductionmentioning
confidence: 99%